2017
DOI: 10.1016/j.joms.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Does Restriction of Public Health Care Dental Benefits Affect the Volume, Severity, or Cost of Dental-Related Hospital Visits?

Abstract: After limitation of dental benefits, there was an increase in the volume and severity of odontogenic infections. In addition, there was an escalated health care cost. The negative public health effects and increased economic impact of eliminating basic dental care show the importance of affordable and accessible preventative oral health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…This comparative study showed that during the COVID-19 lockdown patients persisted with symptoms of CFI of odontogenic origin longer and presented later compared to patients in the pre-COVID-19 era. Studies have shown that patients who do not seek treatment early in CFIs risk a deterioration of their clinical condition 9 , 11 , 12 , 13 . Chen et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comparative study showed that during the COVID-19 lockdown patients persisted with symptoms of CFI of odontogenic origin longer and presented later compared to patients in the pre-COVID-19 era. Studies have shown that patients who do not seek treatment early in CFIs risk a deterioration of their clinical condition 9 , 11 , 12 , 13 . Chen et.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have shown how limiting access to essential primary medical/dental services lead to an increase demand on secondary care 12 . Salomon et al found that patients with limited access to primary healthcare were significantly more likely (OR = 1.48; 95% CI, 1.13-1.94), to require incision and drainage upon admission and had longer hospital admissions (p = 0.004) than those with adequate access 12 . An increase in patients requiring secondary care treatment leads to higher costs, stretching resources in hospitals which could potentially be deployed in the management COVID-19 and ultimately be of further detriment from a health-economics perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients presenting to emergency departments (EDs) with odontogenic infections is increasing (16)(17)(18)(19)(20), which is likely due to a number of factors including cost, fear, mental illness, substance abuse, health literacy and perceptions that oral disease is of low importance (21,22). While some of these patients can be discharged safely from ED for treatment in outpatient clinics, others will require inpatient admission for more urgent incision and drainage of their abscess.…”
Section: Introductionmentioning
confidence: 99%
“…You can freely access the chapter at the Web Viewer here. surgical cares increased 100%, and the related healthcare cost skyrockets [175]. The reported data show that opportunistic species and/or ARIA infections are nearby and expected to increase in dental setting [21-26, 29, 81, 82, 85, 91-99, 101-105, 109-114, 120-124, 136-141, 145-149, 153-155, 159, 160, 165] due to the overuse of antibiotics in dentistry and the limited awareness on infection prevention guidelines and the lapses and errors during infection prevention [176].…”
Section: Resultsmentioning
confidence: 99%